2014
DOI: 10.1016/j.apacoust.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement network for urban noise assessment: Comparison of mobile measurements and spatial interpolation approaches

Abstract: This paper investigates the relevance of different interpolation techniques to improve the spatial resolution of urban noise maps, in complement to measurements achieved at fixed stations. Interpolation techniques based on mobile measurements are compared to usual spatial interpolations techniques, namely Inverse Distance Weighting and Kriging. The analyses rely on a measurement campaign, which consisted of nearly 8 hours of georeferenced mobile noise measurements performed at random moments of the day, conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…The most crucial include the size of the area, the number of points measured as well as their spatial distribution and the way of selecting them (a priori, on site). Although the use of spatial interpolation methods has not been always successful in the prediction of noise levels [25] it has been shown that they can be useful for mapping soundscape quality or particular perceptual attributes in the urban context [24,26]. Definitely the proper soundscape data collection method should be applied according to the scope of the study.…”
Section: Model Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The most crucial include the size of the area, the number of points measured as well as their spatial distribution and the way of selecting them (a priori, on site). Although the use of spatial interpolation methods has not been always successful in the prediction of noise levels [25] it has been shown that they can be useful for mapping soundscape quality or particular perceptual attributes in the urban context [24,26]. Definitely the proper soundscape data collection method should be applied according to the scope of the study.…”
Section: Model Effectivenessmentioning
confidence: 99%
“…What can be taken for sure is that almost in all cases different interpolation methods will produce different results [23]. Since there are no hard and fast rules for soundscape mapping, previous studies have used several interpolation algorithms such as: Kriging [24,25] Inverse Distance Weighted (IDW) [26] or Spline [27].…”
Section: Mapping Toolsmentioning
confidence: 99%
“…The main advantages of mobile measurements for the purpose of refining the spatial resolution of noise maps are discussed in [22]. Compared to fixed stations coupled with classical interpolation methods (e.g.…”
Section: Mobile Noise Measurementsmentioning
confidence: 99%
“…A finer spatial granularity can be obtained experimentally through mobile measurements [22]. In-transit measurements consists in recording noise levels along a journey and involve two main devices: an acoustic sensor (a sonometer usually) and a global positioning system (GPS).…”
Section: Mobile Noise Measurementsmentioning
confidence: 99%
“…Some studies compared the methods which are used to prepare noise maps. These studies focused on the advantages and disadvantages of above mentioned methods with the help of sample implementations (Can et al, 2014;Harman et al, 2016). In the literature, there are various studies that special techniques applications of GIS have been employed to map, monitor and model noise (Akintuyi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%